Relation of ?-Amylase Activity with Glucose and Anti-Gliadin IgA and IgG in Sera of Patients with Celiac Disease - Sura A. Al-Emami; Aliaa H. Faraj; Dahlia M.R. Al-Abadi (College of Pharmacy University of Baghdad, 2017)
Celiac disease (CD) is an inflammatory small intestinal disorder that can lead to severe villous atrophy, and malabsorption . Since the measurement of Î±-amylase activity is the most widely used biochemical test for the diagnosis of pancreatic and non pancreatic disease , therefore serum Î±-amylase were studied in the present study in an attempt to evaluate the usefulness of this enzyme in the diagnosis of celiac disease and its relationship with anti gliadin IgA and IgG and serum glucose . Thirty one patients with celiac disease were studied and compared with twenty four healthy individuals . Significant elevation of Î±-amylase activity , glucose and anti gliadin IgA and IgG were observed in the sera of patients with celiac disease compared with the control group . Also a significant positive correlation between Î±-amylase activity and anti gliadin  IgG were found in the present study in the sera of patients with celiac disease while a non significant correlation were found between Î±-amylase activity and anti gliadin IgA and glucose in the sera of the same patients of celiac disease. Keywords:- Î±-amylase , anti â€" gliadin  IgA , IgG , glucose , celiac disease .